PERANCANGAN ULANG TATA LETAK FASILITAS DI CAFÉ “HOME 232” CINERE - AZAM CHAERUL; BASUKI ARIANTO; W.TEDJA BHIRAWA (JURNAL TEKNIK INDUSTRI, 2021)
Home Cafe 232 is a Cafe engaged in food and beverages and various coffees on Jl H.Therin 1 pangkalan jati Cinere Depok West Java. The problem that exists in this restaurant is the track that is passed by consumers and less efficient servants that cause congestion on the track and this restaurant has not been able to meet demand optimally. Because the layout is still inaccurate, where to make material transfers between departments, the distance needed is far enough so that it takes a long time. Besides that, in setting the layout of production facilities in this restaurant only using experience, this causes the service flow to seem irregular and the coordination relationship between parts is less effective, such as the location of bar / waiters that are too far from the living room. Cashier near the warehouse. With the existence of these problems, the research is carried out with the From To Chart (FTC) method and Activity Relationship Chart (ARC) in the hope of minimizing the length of material trajectory distances and consumers which indirectly can increase the effectiveness and efficiency of work and service flows seem more regular. The layout design results obtained the length of distance in the initial conditions of 133.5 m, while the length of the track distance at the condition of the proposal amounted to 125 m. This means that in the design of the proposed condition layout using the From To Chart (FTC) method and Activity Relationship Chart (ARC) can minimize the length of the path by 8.5 m, from the initial layout conditions.Keywords: Restaurant Layout, Method Of From To Chart (FTC) Method And Activity Relationship Chart (ARC)